PENGEMBANGAN DESA WISATA EDUKATIF BERBASIS MEDIA PROMOSI DIGITAL MELALUI PROGRAM GEMA DI DESA CIDERUM BOGOR - Jati Paras Ayu; Jennifer Helga Hartono; Ferdinando Daniell Kusuma Lanajaya; Amela Inggrid Wibowo; Nadia Agustina (Dharma: Jurnal Pengabdian Masyarakat, 2026)
The “GEMA – Gerakan Aksi Membangun Branding” program was designed to address the challenges faced by Ciderum Tourism Village through strengthening destination branding and enhancing community capacity in marketing the village’s tourism potential in a professional and sustainable manner. The program emphasized the use of digital promotional media, including the development of e-books, e-booklets, and promotional videos, as strategic branding instruments. Ciderum Tourism Village has experienced a decline in tourist arrivals over the past three years, primarily due to the lack of a strong destination identity and limited digital promotional activities. This initiative was implemented by Tourism students from LSPR Institute of Communication and Business using a structured socialization approach conducted through pre-event, main event, and post-event stages. The findings indicate a significant improvement in the digital marketing knowledge and management capacity of the Tourism Awareness Group (Pokdarwis) in Ciderum Tourism Village. Prior to the program, only 30% of Pokdarwis members demonstrated an understanding of digital-based tourism marketing, while after the intervention, the level of understanding increased to 70%. Overall, the program generated a highly positive and sustainable impact on the local community, particularly the Pokdarwis, by strengthening their ability to promote the destination effectively and reinforcing Ciderum’s branding as an educational tourism village in Bogor. Keywords: Educational Tourism Village, Ciderum, Bogor